Cost-effectiveness of community mobilization (Camino Verde) for dengue prevention in Nicaragua and Mexico: A cluster randomized controlled trial. (May 2020) - Tschampl, Cynthia A.; Undurraga, Eduardo A.; Ledogar, Robert J.; Coloma, Josefina; Legorreta-Soberanis, Jose; Paredes-Solís, Sergio; Arosteguí, Jorge; Hernández-Álvarez, Carlos; Harris, Eva; Andersson, Neil; Shepard, Donald S.
Highlights: A community intervention, Camino Verde, significantly reduced dengue cases. Camino Verde proved marginally cost-effective in Mexico within a research program. Camino Verde was not cost-effective in Nicaragua in this research context. By sharing costs with other programs, Camino Verde could become widely cost-effective. Abstract: Background: We assessed the cost-effectiveness of Camino Verde, a community-based mobilization strategy to prevent and control dengue and other mosquito-borne diseases. A cluster-randomized controlled trial in Managua, Nicaragua, and in three coastal regions in Guerrero, Mexico (75 intervention and 75 control clusters), Camino Verde used non-governmental community health workers, called brigadistas, to support community mobilization. This donor-funded trial demonstrated reductions of 29.5% (95% confidence interval, CI: 3.8%–55.3%) on dengue infections and 24.7% (CI: 1.8%–51.2%) on self-reported cases. Methods: We estimated program costs through a micro-costing approach and semi-structured questionnaires. We show results as incremental cost-effectiveness ratios (ICERs) for costs per disability-adjusted life-year (DALYs) averted and conducted probabilistic sensitivity analyses. Findings: The Camino Verde trial spent US$16.72 in Mexico and $7.47 in Nicaragua per person annually. We found an average of 910 (CI: 487–1 353) and 500 (CI: 250–760) dengue cases averted annually per million population in Mexico and Nicaragua, respectively, compared to control communities. The ICER in Mexico was US$29 618 (CI: 13 869–66 898) per DALY averted, or 3.0 times per capita GDP. For Nicaragua, the ICER was US$29 196 (CI: 14 294–72 181) per DALY averted, or 16.9 times per capita GDP. Interpretation: Camino Verde, as implemented in the research context, was marginally cost-effective in Mexico, and not cost-effective in Nicaragua, from a healthcare sector perspective. Nicaragua's low per capita GDP and the use of grant-funded management personnel weakened the cost-effectiveness results. Achieving efficiencies by incorporating Camino Verde activities into existing public health programs would make Camino Verde cost-effective.